FACTORS INFLUENCING POSTSURGICAL ACUTE PAIN AND ITS PHARMACOLOGICAL MANAGEMENT AMONG PATIENT UNDERGOING ELECTIVE SURGERIES AT TERTIARY CARE HOSPITAL MARDAN (The Research of Medical Science Review, 2024)
Background: Postsurgical acute pain is a critical factor impacting recovery, patient satisfaction, and the risk of complications in surgical patients. Effective pain management is essential for enhancing patient outcomes and reducing the likelihood of chronic pain development. However, pain perception is influenced by various factors, including demographic characteristics, type, duration and complexity of surgery, and pharmacological approach. This study aimed to identify these contributing factors and assess the effectiveness of different analgesics in managing postsurgical pain in a tertiary care setting. Methods: A cross-sectional observational study was conducted on 386 patients (38.6% male, 61.4% female) who underwent elective surgeries. Data on demographics, surgical details, pain intensity, and patient satisfaction with pain management were collected. Statistical analyses, including chi-square tests, Fisher exact test and ANOVA, were performed to assess the relationships between pain intensity and various factors, with significance set at p<0.05. Results: The significant factors influencing postoperative pain intensity included sex, body mass index, surgeon experience, duration of surgery, incision length and patient occupation. Notably, pain levels were high post-surgery, with 33.9% experiencing severe pain and 59.1% reporting moderate pain. Ketorolac was the most frequently used analgesic (60.6%), followed by tramadol (30.8%) and nalbuphine (5.9%). Compared with tramadol and nalbuphine, tramadol with adjuvants initially provided significantly better pain relief (p<0.001). Pain intensity decreased over time, with 63.7% of patients reporting no pain at two hours and 44.3% at four hours post-surgery. The satisfaction level was highest in patients administered tramadol combined with an adjuvant. Conclusion: Effective pharmacological interventions, specifically tramadol with adjuvants and ketorolac significantly reduce postoperative pain over time. Patient satisfaction was highest with multimodal approaches combining tramadol and adjuvants, suggesting a preference for comprehensive pain management strategies. Further studies should explore personalized pain management approaches that consider patient demographics and surgical specifics to optimize outcomes.